TECHNOLOGY OF USING OUTDOOR GAMES IN THE DEVELOPMENT OF PHYSICAL QUALITIES OF JUNIOR SCHOOLCHILDREN (Academicia Globe: Inderscience Research, 2022)
The article considers the technology of using outdoor games in the development of physical qualities of younger students. The pedagogical characteristics of outdoor games are proposed in connection with the age characteristics of younger schoolchildren. The health-improving effect of outdoor games on the body of children of primary school age is revealed.